CONSTRUCTIVE EMPIRICISM WITHOUT THE EPISTEMIC COMMUNITY - Bujokas, Justas (Problemos, 2017)
Constructive empiricism (CE), a widely debated anti-realist philosophy of science by Bas van Fraassen, offers a philosophical interpretation of scientific practice. The agent of the scientific practice, according to CE, is what Bas van Fraassen himself calls the “epistemic community”. However, William Seager argued that by appealing to the epistemic community constructive empiricists warrant scientists’belief in unobservables. Moreover, Simone Bahrenberg et al. maintained that if what is observable is defined in terms of whom a particular epistemic community consists of, then observability cannot be an objective property, while CE needs observability to be objective. In this paper, based on four thought experiments, I consider a special hypothetical case of the epistemic community consisting of only one person and notice that in this hypothetical case the objections by Seager and Bahrenberg et al. dissolve: Seager’s requirement to treat the reports of other members of epistemic community as an evidence for the epistemic belief collapses; and, contra Bahrenberg et al., observability for a single person is unproblematically objective in CE. Based on this observation I argue that constructive empiricists would be better off reformulating their main thesis in terms of a single cognitive agent (person, scientist), because (i) this would not only allow CE to render all the objections appealing to the concept of epistemic community ineffectual once and for all, but also (ii) using the proposed modification constructive empiricists could straightforwardly account for some cases of possible scientific practice, for which their original thesis cannot account in an obvious manner. The above change in the policy of CE (iii) would still allow to retain the key features of the empiricist position—the observable/unobservable distinction, the distinction between acceptance and belief, the principles of epistemic modesty and the principle of scientific rationality—at least on an equal footing to the original thesis by van Fraassen.
Keywords: constructive empiricism; epistemic community; observability; objectivity